2022
DOI: 10.3390/foods11244016
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Digestion and Fermentation In Vitro by Obese Human Gut Microbiota of Sulforaphane from Broccoli Seeds

Abstract: Background: sulforaphane is a kind of isothiocyanate, which is obtained by hydrolysis of glucosinolate by the unique myrosinase in plants. It has been proved to prevent the occurrence of many chronic diseases, such as obesity, diabetes and cancer. Objective: The impact of SFN on obese human gut flora, however, has not been established. Methods: In this research, SFN was isolated from broccoli seeds and then refined to achieve 95% purity. Next, an investigation was conducted into the digestion and fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A previous study had shown that Phellinus linteus polysaccharide could effectively inhibit the relative abundance of Escherichia–Shigella , a kind of pathogenic bacteria. In the groups incubated with sulforaphane from broccoli seeds, the relative abundance of harmful bacterium genera, Clostridium_sensu_stricto_1, decreased . Similarly, HSPs could decrease the abundance of these harmful bacterial communities, which might be the key genera for HSP regulation.…”
Section: Resultsmentioning
confidence: 98%
“…A previous study had shown that Phellinus linteus polysaccharide could effectively inhibit the relative abundance of Escherichia–Shigella , a kind of pathogenic bacteria. In the groups incubated with sulforaphane from broccoli seeds, the relative abundance of harmful bacterium genera, Clostridium_sensu_stricto_1, decreased . Similarly, HSPs could decrease the abundance of these harmful bacterial communities, which might be the key genera for HSP regulation.…”
Section: Resultsmentioning
confidence: 98%
“…The exploration of natural compounds and their analogs as chemopreventive agents is gaining momentum. SFN, known for its health benefits, is garnering attention in the medical field, especially for its potential protective effects against various types of cancer [38][39][40][41][42][43], cardiovascular diseases [44][45][46], neurological diseases [47][48][49][50], insulin resistance [51][52][53], obesity [54][55][56], and musculoskeletal diseases [57][58][59]. Additionally, the consumption of broccoli, brussels sprouts, cabbage, and SFN, an isothiocyanate derivative, is linked to various health benefits, including anticancer and antioxidant properties [60].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previously described method Solaesa et al, 2022;Sun et al, 2022), in vitro fermentation was conducted using undigested rice flour. On the day of the fermentation experiment, fresh fecal samples were collected from three obese volunteers aged between 24 and 32 years, with a body mass index of 25-35 kg/m 2 .…”
Section: In Vitro Fermentationmentioning
confidence: 99%
“…The bacterial cell density (OD600) of each type of rice flour after in vitro fermentation as measured at 600 nm using the Spark Multimode Plate Reader (Tecan, Männedorf, Switzerland). The content of SCFAs was determined by gas chromatography as previously described (Chen et al, 2017;Sun et al, 2022). In brief, 1.0 mL of sample was combined with 50 μL of phosphoric acid (34%), and the SCFA content was analyzed using the Shimadzu GC-2014 system (Kyoto, Japan) equipped with a flame ionization detector (FID) and a DB-FFAP column (30 m × 0.25 mm × 0.25 μm).…”
Section: Short-chain Fatty Acids Determinationmentioning
confidence: 99%
See 1 more Smart Citation